Pengembangan Pemasaran Sektor Kepariwisataan pada Dinas Kebudayaan dan Pariwisata Kota Palembang - Wendy Liana (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
The purpose of this research was to know the development of marketing in Department of Culture and Tourism the City of Palembang. This research used quality methods. The data was the primary data and secondary data. Data collection techniques were interview documentation and observation. The result showed that the development of tourism marketing sector were still not enough based on promotional activities carried out of the advertising and sales support which were not optimal. Human resources had been optimal, but just need to be adapted as well as developing tourist village. The development of new products need to be optimized especially in tourism. This research result recommended that the Department of Culture and Tourism the City of Palembang must increase promotion activities, adding to the amount tour guide, and also development of new tour object.